PERANCANGAN PUSAT REHABILITASI NARKOBA KOTA LAMONGAN TEMA ARSITEKTUR PERILAKU - Mimin Aminah Yusuf; Ali as’ad burhanuddin; Ainun Nurin Sharvina; Bhaga Aninditatama (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2023)
Drug addicts are thinking beings who have their own decisions in interacting in their environment, the behavior patterns of drug addicts can be observed and understood according to their needs. The concept of behavioral architecture can be used as a tool to find out that a building, in particular, a drug rehabilitation building can influence the behavior of its users. One of the buildings that applies the concept of behavioral architecture is the Lamongan Regency Rehabilitation House. This rehabilitation building was made by considering the behavior of drug users which can be seen through the interaction of drug users with their environment. This study intends to describe and determine the application of the concept of Behavioral Architecture to the Lamongan District Rehabilitation House building. The method used is descriptive qualitative. In the rooms of the Lamongan District Rehabilitation House, the arrangement of furniture in the room can affect the psychology of drug user behavior. Likewise with the color, sound, temperature and lighting applied to the Lamongan Regency Rehabilitation House building which is very influential for users because it does not create a frightening impression, so it can improve the psychology of drug users. The design of the narcotics rehabilitation center building with the theme of behavioral architecture is designed by prioritizing the concept of behavioral architecture itself which is expected to be able to help users change their personality for the better, improve social life and order in living their daily lives.